Evaluation of polybenzimidazole-based polymers for the removal of uranium, thorium and palladium from aqueous medium. Issue 6 (20th June 2018) - Kumar, V. Vijaya; Kumar, C. Ramesh; Suresh, A.; Jayalakshmi, S.; Mudali, U. Kamachi; Sivaraman, N.
Abstract : Four types of polybenzimidazole (PBI)-based polymers ( m -PBI, p -PBI, pyridine-based m -PBI and alkylated m -PBI) have been prepared and characterized. Extraction behaviour of heavy metal ions, viz. U(VI), Th(IV) and Pd(II), with these polymers was investigated. Distribution ratios for the extraction of these metal ions were measured as a function of nitric acid concentration. Extraction data reveal that, in general, p -PBI exhibits a higher distribution ratio for U(VI), Th(IV) and Pd(II) compared with the other polymeric resins evaluated in the present study. Column chromatography experiments were carried out with a solution of U(VI), Th(IV) and Pd(II) in dilute nitric acid media using columns packed with m - and p -PBI polymeric material for understanding the sorption and elution behaviour. The p -PBI-based resin has shown higher palladium sorption capacity (1.8 mmol g −1 ). The studies also established that p -PBI resin is a potential candidate material for the recovery of U(VI) and Th(IV) (capacity 0.22 mmol g −1 and 0.13 mmol g −1 ) from an aqueous stream, e.g. mine water samples.